Melatonin Protects Methamphetamine-Induced Neuroinflammation Through NF-κB and Nrf2 Pathways in Glioma Cell Line - Pichaya Jumnongprakhon (2018)
© 2015, Springer Science+Business Media New York. Methamphetamine (METH) is known as a toxin for neuronal and glial cells. Previous studies have found that METH-induced glial cell death and inflammation is mediated by oxidative stress. However, the exact mechanisms of the inflammatory response remain unclear. Therefore, we hypothesized that the activation of nuclear factor-κB (NF-κB) signaling, a key mediator of inflammation, and the inhibition of nuclear factor erythroid 2-related factor-2 (Nrf2) signaling, a regulator of the antioxidant response, would be significant events occurring in response to METH-induced inflammation in a rat glioma cell line (C6 cells). Our results show that METH increased the production of nitric oxide (NO) and up-regulated the expression of its main regulatory protein, inducible nitric oxide synthase (iNOS). METH also induced NF-κB activation by increasing inhibitory κBα (IκBα) degradation and translocation of the NF-κB (p65) subunit into the nucleus. Additionally, METH inhibited the activation of the Nrf2 pathway by decreasing the translocation of Nrf2 into the nucleus and also by suppressing the expression of heme oxygenase-1 (HO-1), NAD(P)H quinone oxidoreductase-1 (NQO-1), and glutamate-cysteine ligase catalytic subunit (γ-GCLC), resulting in the suppression of superoxide dismutase (SOD) activity. Pretreatment with melatonin effectively promoted Nrf2 activation and reversed the METH-induced NF-κB response. Melatonin increased the expression of HO-1, NQO-1, and γ-GCLC, resulting in increased SOD activity. In addition, melatonin also decreased IκBα degradation, translocation of the p65 subunit, and expression of iNOS, resulting in decreased NO production. Taken together, our results indicate that melatonin diminishes the proinflammatory mediator in METH-stimulated C6 cells by inhibiting NF-κB activation and inducing Nrf2-mediated HO-1, NQO-1, and γ-GCLC expression.